R,D&I in Electric Sector: a Management Model - Moraes, Edmilson Alves de; Varela, Carmen Augusta (Journal of Technology Management & Innovation, 2013)
This study was carried out with the support of the companies of Eletrobras (Chesf, Furnas, Eletronorte and Eletrosul) and seeks to develop an integrated management model that incorporates technology and innovation. The model should be concerned with the performance of companies, aligning R, D&I [Research, Development and Innovation] projects with business strategies. The project was undertaken by an in-depth bibliographical review of the subject and a series of guided interviews. These interviews were conducted in both national and international companies that were regarded as innovative in several different sectors, in an attempt to identify practices that could be employed by companies in the electric sector. The findings of this research allowed the development of an integrated R,D&I Management model which is formally set out here as the results of this study.